The Impact of Corruption and Financial Inclusion Interaction on Poverty in Africa’s Most Unbanked Nations - Abdullahi Sakanko, Musa; Abu, Nurudeen; Gamal, Awadh Ahmed Mohammed; Rufai Mohammed, Salimatu (Organizations and Markets in Emerging Economies, 2025)
Financial inclusion (FI) has been widely advocated as a means of improving poor economic possibilities, smoothing investments and savings, and providing a safety net against economic shocks. Despite the empirical evidence supporting the benefits of FI on poverty reduction, less attention has been paid to the role of control of corruption (CRR) on FI and poverty nexus. We evaluate the influence of CRR on the FI–poverty relation in Africa’s most unbanked nations (i.e. Egypt, Kenya, Morocco, Nigeria, and South Africa) from 2004 to 2022. Using panel regressions such as DOLS and FMOLS estimators, the results portray that FI is more effective in reducing poverty at greater CRR, whereas FI has the opposite effect at the least CRR. Other core drivers of poverty include GDP per capita growth, inflation, and money supply. The coefficients of the variables of interest (i.e. financial inclusion, control of corruption, and their interaction) show consistency in terms of size, signs, and significance, suggesting robustness in the results. Thus, Africa’s governments and relevant authorities are advised to control corruption to ensure effective poverty reduction impact of financial inclusion. This will guarantee that intended groups receive the benefits of financial inclusion, leading to poverty reduction.